Spatiotemporal dynamics of triatomines (Hemiptera: Triatominae), vectors of Chagas disease in Sergipe, Brazil (2005-2023) - de Melo, Cláudia Moura; Fontes, Felipe Mendes; Santos, Natália Almeida Frota; de Lourdes Sierpe Jeraldo, Verónica; dos Santos, Renato Elias; de Oliveira, Jader [UNESP]; dos Santos Gabriel, Rosemeire; Moura, Karine Dantas; Madi, Rubens Riscala; da Rosa, João Aristeu [UNESP] (Sociedad Chilena de Entomologia, 2025)
Chagas disease remains a significant public health challenge in Brazil, especially in the state of Sergipe, where vector transmission continues to be the main route of infection. This study analyzed the spatiotemporal distribution of triatomines between 2005 and 2023, using historical data from the Central Public Health Laboratory of Sergipe (LACEN/SE). A total of 2,498 triatomines were collected from 1,353 households, with a predominance of captures in the intradomiciliary environment (67.9%). Most specimens were adults (86.7%). The most frequent species were Triatoma pseudomaculata (41.2%), Panstrongylus lutzi (24.1%), Triatoma brasiliensis (17.5%), and Panstrongylus megistus (10.7%). The intradomiciliary infestation averaged 88.9%, reaching 100% in some years, while peridomiciliary infestation was 14.6%. The Mann-Whitney test indicated significant differences in species distribution between intra- and peridomiciliary environments. An average annual decline of 13.49 triatomines was observed in the number of kissing bugs collected in households, according to the slope coefficient of the simple linear regression (r² = 0.6859; p < 0.001). Furthermore, simple linear regression analysis revealed a positive trend between the number of triatomines collected and the number of notified households over the years. Annual fluctuations in the number of triatomines captured were also observed, with a peak in 2009 and the lowest record in 2023. The results highlight the need to strengthen surveillance actions, vector control measures, and community education strategies adapted to the local context to prevent the transmission of Chagas disease.